PENGELOLAAN DAN PEMANFAATAN MEDIA ONLINE UNTUK MEMBANGUN DAN MENGKOMUNIKASIKAN MEREK UMKM JOGJA CRAFT CENTER - Mala Fajriyah (2011)

(untitled)
This research is mainly about how middle small micro company of Jogja Craft Center manages and uses an online media to develop and establish a brand. This type of research uses qualitative and descriptive method which explains, describes and elaborates anything related to the research with the research objective toward middle small micro company of Jogja Crapt Center located in Ngemplak Yogyakarta. The aim of the research is: 1) to describe on how Jogja Craft Center manages and uses online medi